ANALISIS HUBUNGAN ANTARA LAPORAN LABA RUGI PERUSAHAAN TAMBANG BATUBARA DENGAN SETORAN PPH BADAN PADA KPP PRATAMA SAMARINDA - Heriyanto., Ahmad Albara Dipayana, LCA Robin Jonathan (EKONOMIA, 2017)
The purpose of this study is to know and analyze: (1) the effect of income statement elements (total sales, gross profit, maintenance expense, depreciation expense and net income) partially to the amount of corporate income tax (2) the effect of income statement elements (total sales, gross profit, maintenance expense, depreciation expense and net income) simultaneously to the amount of corporate income tax.The technique of data collecting was done by using method of documentation. Prior to analysis, prerequisite analysis test is done included normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. Analysis of data that used to test the hypothesis is using multiple regression analysis techniques.Based on the results of data analysis can be concluded that the sales and net profit variables partially significant affect the amount of corporate income tax, this is indicated by the value of t-count of sales 2.092 and t-count of net profit 5.960 are greater than t-table 2.0639. Gross profit, maintenance expense and depreciation expense variables have no significant effect to the amount of corporate income tax, this is indicated by the t-count of gross profit 0.210, the t-count of maintenance expense -0.268, and the t-count of depreciation expense 1.541 are smaller than the t-table 2.0639. The research conclusion of this hypothesis is rejected.Meanwhile, simultaneously all the independent variables such as sales, gross profit, maintenance expense, depreciation expense, and net profit have a significant effect on the amount of corporate income tax, this is indicated by F-count 47.81 are greater than F-table 2.62. The research conclusion of this hypothesis is accepted.